Perspectives that Influence Action Plans for Chronic Obstructive Pulmonary Disease - S Costi; D Brooks; RS Goldstein (Canadian Respiratory Journal)
BACKGROUND: Prompt treatment of acute exacerbations (AEs) in chronic obstructive pulmonary disease (COPD) improves quality of life and reduces the use of health care resources. Although patient self-management through an individualized action plan (AP) can help with early initiation of therapy, its use is critically dependent on the patient recognizing the features of an exacerbation.